Efficient Bioelectrochemical Conversion of Industrial Wastewater by Specific Strain Isolation and Community Adaptation - Brunner, Stefanie; Klessing, Tina; Dötsch, Andreas; Sturm-Richter, Katrin; Gescher, Johannes (Frontiers in Bioengineering and Biotechnology, 2019)
The aim of this study was the development of a specifically adapted microbial community for the removal of organic carbon from an industrial wastewater using a bioelectrochemical system. In a first step, ferric iron reducing microorganisms were isolated from the examined industrial wastewater. In a second step, it was tested to what extent these isolates or a cocultivation of the isolates with the exoelectrogenic model organism Geobacter sulfurreducens (G. sulfurreducens) were able to eliminate organic carbon from the wastewater. To establish a stable biofilm on the anode and to analyze the performance of the system, the experiments were conducted first under batch-mode conditions for 21 days. Since the removal of organic carbon was relatively low in the batch system, a similar experiment was conducted under continuous-mode conditions for 65 days, including a slow transition from synthetic medium to industrial wastewater as carbon and electron source and variations in the flow rate of the medium. The overall performance of the system was strongly increased in the continuous- compared to the batch-mode reactor and the highest average current density (1368 mA/m2) and Coulombic efficiency (54.9%) was measured in the continuous-mode reactor inoculated with the coculture consisting of the new isolates and G. sulfurreducens. The equivalently inoculated batch-mode system produced only 82-fold lower current densities, which were accompanied by 42-fold lower Coulombic efficiencies.